The Extent to which Faculty Members at Jordanian Public Universities Promote Intellectual Security among Students - Muneera AL Shdefat (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to measure the degree to which faculty members in Jordanian public universities promote intellectual security of their students. A questionnaire consisting of (21) items was developed and distributed to three areas (faculty members, university administration, and university courses). The study population consisted of all students from Jordanian public universities; the study was applied to a sample from Yarmouk University, the University of Jordan and Mutah University (n=80281) during the first semester of the academic year 2019/2020. A simple random sample of (382) male and female students was chosen. In addition, an exploratory interview was conducted with thirty faculty members chosen by a simple random method to measure the obstacles to enhancing students' intellectual security from the viewpoint of faculty members. The results of the study showed that the degree to which faculty members at public universities in Jordan promote intellectual security among their students from the students' point of view was moderate. The results showed the existence of obstacles, the most important of which is the widespread use of social networks among students, the multiplicity of nationalities and cultures among university students, and the confinement of lectures to the scientific material presented. In light of the results, the researcher recommends adding a university course to the programs at public universities entitled Intellectual Security..